2015
DOI: 10.3892/ol.2015.3179
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of tumor suppressor and oncogenic miRNAs in gastric cancer

Abstract: Abstract. The aim of the present study was to screen for and identify microRNAs (miRNAs/miRs) that are associated with gastric cancer and to clarify the role of these miRNAs in gastric cancer. Thus, the differential expression of a panel of miRNAs in two pairs of gastric cancer tissues and their matched adjacent healthy tissues was investigated by performing a microarray analysis. To verify the results of this screen, 56 gastric cancer tissues were analyzed for the selected miRNAs using reverse transcription-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Downregulation of miR‐133b had also been observed in other cancers, including colorectal cancer, gastric cancer, and renal cell carcinoma 19, 20, 21. Furthermore, we found downregulation of miR‐133b associates with aggressive clinicopathological features of UCB.…”
Section: Discussionsupporting
confidence: 67%
“…Downregulation of miR‐133b had also been observed in other cancers, including colorectal cancer, gastric cancer, and renal cell carcinoma 19, 20, 21. Furthermore, we found downregulation of miR‐133b associates with aggressive clinicopathological features of UCB.…”
Section: Discussionsupporting
confidence: 67%
“…Although there are currently no signaling pathways associated with miR-95 or miR-551b-3p in the current KEGG database, these miRNAs are also reported to be tumor suppressors. 51 With the exception of miR-126-3p, none of these miRNAs has previously been reported as associated with tobacco use. A further 14 miRNAs were differentially expressed with P values less than 0.1.…”
Section: Discussionmentioning
confidence: 94%
“…It is pointed out that hsa‐miR‐139‐5p shows decreased expression associated with STAD . Previous reports found that hsa‐miR‐145 was a potential tumor suppressor and hsa‐miR‐145‐3p and hsa‐miR‐145‐5p were down‐regulated in stomach carcinoma . Kuo et al .…”
Section: Discussionmentioning
confidence: 96%
“…It is pointed out that hsa-miR-139-5p shows decreased expression associated with STAD [22,23]. Previous reports found that hsa-miR-145 was a potential tumor suppressor and hsa-miR-145-3p and hsa-miR-145-5p were down-regulated in stomach carcinoma [24][25][26]. Kuo et al [22] demonstrated that hsa-miR-490-3p was down-regulated in STAD gastric carcinoma tissues.…”
Section: Discussionmentioning
confidence: 98%